Electricity reforms and firm level responses: changing ownership, fuel choices, and technology decisions. (21st April 2005) - Shukla, P.R.; Nag, Tirthankar; Biswas, Debashish
This paper examines how electricity reforms in India managed to influence the responses of generating firms. Indian electricity reforms have federal and state character. This paper utilises an extensive survey of generation units in Gujarat State. The findings suggest that reforms have created heterogeneous ownership of generation units. The fuel-mix and technology choices of new owners differ from pre-reform pattern followed by state-owned utilities. The new owners prefer natural gas, sourced technologies internationally, and chosen unit sizes that follow market dynamics. Consequently, the operational performance of power plants has improved. This paper quantifies energy efficiency and carbon intensity baselines, projects their trends, and delineates the contribution of reforms for the state. In generalisation, this paper argues that energy and cost efficiency of power plants across different states shows secular improvements under the reforms, though it cautions that environmental performance would not show such uniformly improving trends.